Psychoanalysis, Lacan, and social theory - Hayes, Grahame (PINS-Psychology in Society, 2025)
Psychoanalysis has always been in the news! And once again it has achieved a lot of notice, dare one say fame even, within certain variants of social theory. This has been especially so in recent cultural studies with an interest in and "use" of Jacques-Marie Lacan’s work. This article aims to be an introduction to the psychoanalytic work of Lacan, and at the same time offers a warning against some of the appropriations, or rather misappropriations, of Lacanian psychoanalysis in the social theory adumbrated by cultural studies. While this article will discuss the general problems of Lacanian psychoanalysis in the social theory of cultural studies, specific reference will be made to the some of the work of the Contemporary Cultural Studies Unit at the University of Natal in Durban to give the force of my arguments more empirical substance (* see note at the end of the article).